Client-centricity in public administration: communications of government authorities and citizen reactions in the social network "VKontakte" - Roslyakova, Marina Valentinovna (Право и политика, 2025)
A client-centric state, formed within the framework of the federal project "State for People," is focused on effectively meeting the needs of citizens and improving the activities of government structures based on feedback and studying customer experience. Authorities use and adapt the tools and terminology of the client-centric approach, taking into account the experiences of commercial organizations. The article analyzes the public communication of government authorities regarding client-centricity in the social network "VKontakte" and the perception of this new approach to public administration by citizens. The aim of the work is to analyze the content of publications by federal executive bodies (FEB) on their official pages on "VKontakte" regarding client-centricity and to study citizens' reactions to these messages. Based on content analysis and comments in the social network, discrepancies were identified between the declared client-centricity of the authorities and citizens' opinions, which affects the level of trust in state initiatives. Monitoring of the official pages of 62 FEBs in the social network "VKontakte" was conducted. The search was carried out using the keyword "client-centricity" (both automated and manual methods), identifying 234 publications and 2,947 comments. Based on the obtained data, quantitative (posts, comments, reactions) and qualitative content analysis focused on specific phenomena were conducted. The novelty of the work lies in the analysis of the content of official pages of FEBs and citizen feedback on the topic of client-centricity. The study showed that despite promoting the concept of client-centricity as a new citizen-oriented approach in the work of government bodies, citizens express concerns about the potential formalization of the approach and the lack of real improvements in their lives. A qualitative analysis of comments showed a predominance of critical reactions with a minimal number of positive responses. Citizens indicate the ignoring and limiting of comments on the pages of FEBs, which contradicts the principles of client-centricity. The research confirms the need to demonstrate visible results to citizens, ensure prompt feedback, and maintain openness to enhance the effectiveness of communication from FEBs. The results obtained can be used to develop measures to improve public communications of government authorities on social networks. The results contribute to the understanding of the processes of transformation in public administration and the associated complexities and barriers.